Evaluating silage oil from rainbow trout (Oncorhynchus mykiss) viscera as a substitute for dietary fish oil on production parameters of juvenile African catfish (Clarias gariepinus) - Patience, Ashley O'Brian (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.